2021
DOI: 10.3390/jcm10225381
|View full text |Cite
|
Sign up to set email alerts
|

TEG®, Microclot and Platelet Mapping for Guiding Early Management of Severe COVID-19 Coagulopathy

Abstract: An important component of severe COVID-19 disease is virus-induced endothelilitis. This leads to disruption of normal endothelial function, initiating a state of failing normal clotting physiology. Massively increased levels of von Willebrand Factor (VWF) lead to overwhelming platelet activation, as well as activation of the enzymatic (intrinsic) clotting pathway. In addition, there is an impaired fibrinolysis, caused by, amongst others, increased levels of alpha-(2) antiplasmin. The end result is hypercoagula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(105 citation statements)
references
References 104 publications
8
97
0
Order By: Relevance
“…Coagulopathies [ 84–102 ], and especially the formation of extensive microclots in vivo , are a hallmark of both COVID [ 85 , 103–115 ] and long COVID [ 116 , 117 ], and we have demonstrated that these microclots too are amyloid in character [ 108 , 109 , 116 ]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [ 118 ] that adopt amyloid states that are also resistant to fibrinolysis [ 108 ].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 99%
See 3 more Smart Citations
“…Coagulopathies [ 84–102 ], and especially the formation of extensive microclots in vivo , are a hallmark of both COVID [ 85 , 103–115 ] and long COVID [ 116 , 117 ], and we have demonstrated that these microclots too are amyloid in character [ 108 , 109 , 116 ]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [ 118 ] that adopt amyloid states that are also resistant to fibrinolysis [ 108 ].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 99%
“…The size of these amyloid microclots, that can be observed microscopically and stained e.g. with thioflavin T [ 108 , 109 , 116 ] ( Figure 4 ; control vs LC plasma), are typically anywhere from 1–200 µm; this means that they can effectively block up, and inhibit blood flow through, all kinds of microcapillaries, thereby strongly lowering the availability of oxygen in tissues. As expected, they consist mainly of fibrin, but also contain many other proteins, including α2-antiplasmin [ 108 ] (and even the virus itself [ 119 ]).…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it is very difficult to provide laboratory guidance in a number of clinical situations such as liver transplantation, cardiac trauma and obstetrics and particularly with regard to the care of the COVID-19 patient. Viscoelestic testing (VET) methods such as Thromboelastography (TEG) and Rotational Thromboelastometry (ROTEM) provide deeper insight into these subtle coagulopathic changes and have demonstrated that COVID-19 patients develop a propensity for hypercoagulation [6][7][8][9][10][11][12][13][14]. Herein we provide structural images of what may connect the COVID-19 patient's hypercoagulopathy with pneumonia and other organ system failure.…”
Section: Introductionmentioning
confidence: 99%